Adoptive transfer of zoledronate-expanded autologous Vγ9Vδ2 T-cells in patients with treatment-refractory non-small-cell lung cancer: a multicenter, open-label, single-arm, phase 2 study. Issue 2 (18th September 2020) - Kakimi, Kazuhiro; Matsushita, Hirokazu; Masuzawa, Keita; Karasaki, Takahiro; Kobayashi, Yukari; Nagaoka, Koji; Hosoi, Akihiro; Ikemura, Shinnosuke; Kitano, Kentaro; Kawada, Ichiro; Manabe, Tadashi; Takehara, Tomohiro; et al.
Abstract : Background: Not all non-small cell lung cancer (NSCLC) patients possess drug-targetable driver mutations, and response rates to immune checkpoint blockade therapies also remain unsatisfactory. Therefore, more effective treatments are still needed. Here, we report the results of a phase 2 clinical trial of adoptive cell therapy using zoledronate-expanded autologous Vγ9Vδ2 T-cells for treatment-refractory NSCLC. Methods: NSCLC patients who had undergone at least two regimens of standard chemotherapy for unresectable disease or had had at least one treatment including chemotherapy or radiation for recurrent disease after surgery were enrolled in this open-label, single-arm, multicenter, phase 2 study. After preliminary testing of Vγ9Vδ2 T-cell proliferation, autologous peripheral blood mononuclear cells were cultured with zoledronate and IL-2 to expand the Vγ9Vδ2 T-cells. Cultured cells (>1×10 9 ) were intravenously administered every 2 weeks for six injections. The primary endpoint of this study was progression-free survival (PFS), and secondary endpoints included overall survival (OS), best objective response rate (ORR), disease control rate (DCR), safety and immunomonitoring. Clinical efficacy was defined as median PFS significantly >4 months. Results: Twenty-five patients (20 adenocarcinoma, 4 squamous cell carcinoma and 1 large cell carcinoma) were enrolled. Autologous Vγ9Vδ2 T-cell therapy was administered to all 25 patients, of which 16 completed the foreseen course of 6 injections of cultured cells. Median PFS was 95.0 days (95% CI 73.0 to 132.0 days); median OS was 418.0 days (179.0–479.0 days), and best overall responses were 1 partial response, 16 stable disease (SD) and 8 progressive disease. ORR and DCR were 4.0% (0.1%–20.4%) and 68.0% (46.5%–85.1%), respectively. Severe adverse events developed in nine patients, mostly associated with disease progression. In one patient, pneumonitis and inflammatory responses resulted from Vγ9Vδ2 T-cell infusions, together with the disappearance of a massive tumor. Conclusions: Although autologous Vγ9Vδ2 T-cell therapy was well tolerated and may have an acceptable DCR, this trial did not meet its primary efficacy endpoint. Trial registration number: UMIN000006128